Clinical outcomes of bone transport using rail fixator in the treatment of femoral nonunion or bone defect caused by infection - Yalikun, Ainizier; Ren, Peng; Yushan, Maimaiaili; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2023)
Abstract purpose : Rrail fixator system can improve the treatment outcome and provide good stability in patients with femoral bone transport.The purpose of this study is to investigate the clinical outcomes of bone transport using Ilizarov technique by rail fixator system in the treatment of femoral nonunion or bone defect caused by infection. Methods: Clinical feature and treatment outcomes of 32 consecutive adult patients with femoral nonunion or bone defect caused by infection from January 2012 to January 2019 at minimum of 2 years follow-up were retrospectively analyzed. Data were collected on participant’s demographic details. All difficulties that related to bone transport were documented according to Paley’s classification. The clinical outcomes were evaluated using ASAMI criteria at last clinical visit. Results: All 32 patients with an average follow up of 33.54 months. There were 17 problems, 21 obstacles and 8 complications, and complication rate per patient was 1.44. The main complications were pin-site infection (53.13%), axial deviation (21.88%), joint stiffness (18.75%), delayed union of the docking site (18.75%)，soft tissue incarceration(15.63%), delayed consolidation(6.25%), malunion(6.25%), and refracture (3.13%). All the patients achieved bone union, and no recurrence of infection was observed.The excellent and good rates of ASAMI bone and functional results were 87.50% and 81.25%, respectively. Conclusion: Bone transport using Ilizarov technique is an effective method for the treatment of femoral nonunion or bone defect caused by infection，and rail fixator system have obtained satisfactory results in terms of bone and functional results.